2018
DOI: 10.1186/s40880-018-0286-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided fine needle aspiration of retropharyngeal lymph nodes after radiotherapy for nasopharyngeal carcinoma: a novel technique for accurate diagnosis

Abstract: BackgroundEnlarged retropharyngeal lymph nodes (RLNs) are very common in patients with nasopharyngeal carcinoma (NPC) undergoing radiotherapy. The most suitable treatment option for enlarged RLNs depends on the pathological results. However, RLN sampling is difficult and imminent in the clinic setting. We recently developed a novel minimally invasive technique termed endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) for sampling RLN tissues sufficient for pathological or cytological diagnosis.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The limitations of this study included the lack of radiologic-histopathologic correlation data. The feasibility of histological confirmation before ongoing chemotherapy or RT for LRPNs in newly diagnosed NPC is still lacking, although several biopsy methods had been reported; still, several procedures could be safe [31][32][33][34][35]. However, these procedures are only applied to the recurrent LRPNs and not for new cases before RT.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of this study included the lack of radiologic-histopathologic correlation data. The feasibility of histological confirmation before ongoing chemotherapy or RT for LRPNs in newly diagnosed NPC is still lacking, although several biopsy methods had been reported; still, several procedures could be safe [31][32][33][34][35]. However, these procedures are only applied to the recurrent LRPNs and not for new cases before RT.…”
Section: Discussionmentioning
confidence: 99%
“…This group of patients faces a clinical dilemma. Because lymphadenopathy may harbor disease or merely appear as post-treatment necrosis or hyaline fibrosis without viable tumor cells [1416, 19], it may be difficult to define the nature of the cervical masses due to post-irradiation changes in neck soft tissues [15, 18, 19]. Furthermore, since most studies have focused on the efficacy and safety of neck dissection in this group of patients, there is no commonly accepted method for post-treatment determination of malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies comparing HFUS findings with histology found a high intra-observer correlation [14]. When a biopsy is needed to confirm the diagnosis, HFUS can aid the choice of the most inflamed sites for sample collection, as is performed in other organs, such as the liver, breast, or lymph nodes [26,27]. The main weakness of HFUS is that it is operatordependent, and expertise requires previous training [19,28].…”
Section: Discussionmentioning
confidence: 99%